Study on physical and mechanical properties of Nephelium Lappaceum L. Wood after oven-dried and oil heat treatment - Wan Ahmad Wizan, Wan Amira Shaerah (2018)
Rambutan ( Nephelium lappaceum L.) is a popular tropical fruit in the Sapindaceae family, and closely related to litchi, longan, and pulasan. This research had been done because of the lack information about the heat treatment that related with the Asian fruit and the types of treatments that being used. The two types of heat treatment that been used in this experiment are Oven-Dried method and Oil-heat treatment. The temperature that had been used for both heat treatment are 160°C, 180°C and 200 °C. From the experiment, the 160°C and 180°C have a significant values for the moisture content and volume shrinkage test while the temperature of 200 °C is not significant. This might be happen because the temperature of 200 °C are too high and can exposed the skin of the sample to be burnt by the fire. Instead of that, the test of density for all temperature give unsignificant result. This research had been done to compare the best heat treatment between both treatment to the rambutan tree. Besides that, both of these treatment can help to improve the physical and mechaical properties of the wood species. The trees that being choose are 5-10 years old. The samples for bending test were prepared by cutting them into the size of 300 mm longitudinally x 20 mm radially x 20 mm tangentially while 60 mm longitudinally x 20 mm radially x 20 mm tangentially for compression test following ASTM (ASTM 2017) and air drying to about 15% moisture content (Wahab et al., 2012). 54 test blocks of size 20 mm x 20 mm x 30 mm following ASTM D1761-12 (2017) were prepared for all physical test for both method of heat treatments that are oven-dried and oil heat treatment. For the conclusion, the Oil-heat treatment had a better result compared to the Oven-dried method whereas the cost also more cheaper and suitable with the Asian peoples.